Homeworking: negotiating the psychological contract. (8th July 2012) - Collins, Alison M.; Cartwright, Susan; Hislop, Donald
<x xml:space="preserve">Abstract</x> This article explores the psychological contract of female clerical homeworkers who work from home full‐time and are employed at a local authority. Qualitative interviews were carried out with homeworkers and their supervisors. Temporal flexibility was desired by all the homeworkers in order to achieve a better work–life balance, and was deemed important by women without children as well as those with childcare responsibilities. Our findings highlight that homeworkers were able to negotiate their own idiosyncratic deals with line managers in order to attain their desired levels of temporal flexibility. However, the issue of flexibility remains ambiguous with some supervisory staff being more comfortable with the concept than others, leading to some homeworkers enjoying different levels of temporal flexibility than their co‐workers. Our findings suggest that employees perceive flexibility idiosyncratic deals of co‐workers as fair as long as they achieve their own personal levels of temporal flexibility. The potential implications for organisations are discussed.